Novel "Enhanced-Cognition" RFID Architectures on Organic/Paper Low-Cost Substrates Utilizing Inkjet Technologies. (18th November 2007) - Yang, Li; Rida, Amin; Vyas, Rushi; Tentzeris, Manos M.
Abstract : The purpose of this paper is to present an overview of novel design and integration approaches for improved performance "enhanced-cognition" UHF passive and active radio frequency identification (RFID) tags. Antenna design rules are explained for a variety of applications. A strategy that is currently under development for embedding power sources and integration of sensors and integrated circuits (ICs) on low-cost organic substrates, such as liquid crystal polymer (LCP) and paper, enabling the use of inkjet-printing capability for the UHF frequency band, is discussed in the paper. The proposed technologies could potentially revolutionize RFID tags allowing for integrated sensing capabilities for various applications such as security, military, logistics, automotion, and pharmaceutics.